Gender, psycho-emotional impacts and experiences associated with COVID-19 in adults from Guadalajara, Mexico - Gutiérrez, Bersabee Aguirre (2021)
Background: COVID-19 is a virus that not only affects physical health, but also impacts people's psycho-emotional health and daily life, altering family, work, relationship, educational and learning dynamics, among many others. Objetive: This study sought to determine gender differences in terms of psycho-emotional impacts and experiences related to the COVID-19 pandemic in the adult population of the metropolitan area of Guadalajara, Mexico. Method: A qualitative study was implemented, with theory based on the data, through semi-structured interviews (ten women and three men) and through a non-probabilistic convenience sampling. Results: It stands out that the experience related to COVID-19 has generated negative emotions, couple conflicts and discomfort associated with the inability to carry out recreational activities. In the case of women, their routines have been disrupted and they have had a greater demand for the care and attention of their children (in terms of carrying out schoolwork, time spent together, etc.). In contrast, men show greater concern about the difficulty of working from home. Conclusion: The pandemic has impacted men and women differently, in the face of this new reality it is essential to activate the support elements that facilitate the externalization of mobility limitations, changes in the rhythm of life, emotional impact and stressful elements that the experience of COVID-19 could generate in the population.